Islamic Religious Education In Prisons: A Strategy For Mental Rehabilitation Of Drugs Incidents - Khalid H.Minabari; Rusdi Naemuddin; Safri Miradj; Naufandi H. Saleh (At-Tarbiyat, 2022)
The focus of this research is the Class IIB Tobelo Correctional Institution, because so far many drug users who have been fostered in the Class IIB Tobelo Correctional Institution have not succeeded in mental development. This is evident, when they leave the prison there is no change in mental and spiritual. In fact, they tend to return to normal as drug users. Inmates are members of the community who are temporarily exiled based on a judge's decision, with the aim of protecting the community. In prison, the inmates experience several sufferings that are almost never experienced before becoming prisoners, so that their psychological condition will be disturbed and result in mental disorders. In its implementation, the Head of the Kalapas Penitentiary will appoint and determine the Correctional Officer who serves as the Guardian of the Prisoners. The inmate guardian will carry out when the perpetrator of the crime is a prisoner and also the Correctional Inmates as long as the Correctional Inmates undergo a criminal period and the coaching process in interacting and communicating with fellow Correctional Inmates, officers, families and the community. The Correctional Guardian has the obligation to: Record the identity, background of criminal acts, background of social life and also explore the potential of the Correctional inmates with the aim that it can be developed and harmonized with the coaching program; b. Observing, observing, noting the development of coaching, changes in behavior in a positive direction, the relationship of Prisoners with their families and communities, and compliance and obedience to the rules and regulations in prisons.